EVALUASI PENDIDIK TERHADAP PROSES PELATIHAN AIRCRAFT MAINTENANCE TRAINING ORGANIZATION (AMTO) PADA PROGRAM STUDI DIPLOMA TEKNIK AERONAUTIKA - Doni Wildan Hidayat; Sri Yanthy Yosepha (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The purpose of this research is to evaluate the program of incorporating the Implementation of Aircraft Maintenance Training (AMTO) into the aeronautical engineering diploma study program and to find out the extent to which the requirements for educators at UNSURYA (Dirgantara Marshal Suryadarma University) are implemented in supporting the establishment of a recognized or approved D-3 AMTO UNSURYA by the Ministry of Transportation of the Republic of Indonesia and the Ministry of Research Technology and Higher Education of the Republic of Indonesia. With a qualitative approach through evaluative methods and the CIPP model (context, input, process, product) usingdocumentation, interview, observation and questionnaire methods. From this research results and conclusions were obtained about aspects of human resources, aspects ofreadiness, aspects of obstacles, and aspects of competency standardization. The results of the evaluation show that there are still requirements that have not been met, especially the aspect of educator requirements in the implementation of AMTO at UNSURYA, which hinders the process ofgranting AMTO establishment permits.